Normalized Statistical Evaluation of Machining Parameters and Cutting Forces in Turning - Namboodri, Tanuj; Felho, Csaba; Kumar, Ashwani (Manufacturing Technology Journal, 2026)
Investigation of cutting forces in metal cutting is of great importance for defining the effectiveness of the production as well as its impact on product quality. Several researchers studied the effect of cutting parameters on the cutting forces through statistical analysis; however, very few studies use the normalization of the data. Normalization reduces the skewness in the data and increases the accuracy of the results, which can be beneficial in modern industry where AI is being integrated with manufacturing. This research aimed to study the statistical analysis of cutting parameters and cutting forces using log-normalization and compare the accuracy of results with absolute data. The study uses a three-axis piezoelectric dynamometer to measure the cutting forces in the turning of X5CrNi18-10 steel. The results suggested that feed influences the cutting forces during machining. Coolant helps to reduce the cutting forces during the turning of hard steel. Log-normalization increases the accuracy of the results. These results can be used to predict cutting forces during the turning of chromium-nickel alloy steel.
Keywords: Statistical Analysis; Cutting Forces; Tangential Force; Log-normalization; Turning Operation